ความหลากหลายของผึ้งและชันโรง และแหล่งต้นไม้ที่ผึ้งและชันโรงเก็บยางเพื่อใช้ในการผลิตโพรโพลิส ในพื้นที่โครงการอนุรักษ์พันธุกรรมพืชอันเนื่องมาจากพระราชดำริฯ - สุรีรัตน์ เดี่ยววาณิชย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
From this survey biodiversity of bees and stingless bees and the resin from plants to build the propolis in the study site Vagiralongkorn Dam, Khanjanaburi province in November 2010, February, May and August 2011. Apis dorsata, A. cerana and A. florae were found in this site which classified in the genus Apis. The stingless bees were found 5 species such as Tetragonula pagdeni, Tetragonula fuscobalteata, Trigona thoracica, Heterotrigona itama และ Lisotrigona furva. In addition, Amegilla spp. and Nomia spp. were found in this study. Density independent dispersal in all study sites. At Present, Analyzing the composition of resin from plants has been studied.